GREEN SATISFACTION AND LOYALTY IN THE WEST SUMATERA HOSPITALITY INDUSTRY THROUGH THE ROLE OF GREEN TRUST, WOM AND GREEN IMAGE - Thesa Alif Ravelby; Yasri Yasri; Vidyarini Dwita; Deni Suwandhani; Astri Yuza Sari; Muthia Roza Linda; Riza Yonita; Suhery Suhery; Sutiyem Sutiyem; Dessy Trismiyanti (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
Five variables are discussed, namely: Green satisfaction (GS), Green Image (GI), WOM, Loyalty, and Green Trust (GT). The type of research in this study is quantitative causal research. The population of this study were people who had stayed at hotels in West Sumatra. At the same time, the sampling technique used in this research is non-probability sampling. Based on the hypothesis testing proposed, the path analysis technique was used in this study. The first hypothesis is that GT has no significant effect on GS. The second hypothesis is that WOM has a positive impact on GS. The third hypothesis, GI has a substantial effect on GS. The fourth hypothesis, GT is having no significant impact on Loyalty. The fifth hypothesis, WOM has a positive impact on Loyalty. The sixth hypothesis, GI has a positive impact on Loyalty. The seventh hypothesis, GS has a positive impact on Loyalty. The eighth hypothesis, GS is unable to mediate GT on loyalty. The ninth hypothesis, GS is able to mediate the WOM relationship on loyalty. The tenth hypothesis, GS is able to mediate the relationship between GI on loyalty.